The evolution of regional awareness and regionalism in Southeast Asia / Ito Mitsuomi - Ito , Mitsuomi (2017)
This study examines the manner in which politicians and intellectuals in four ASEAN founding member countries, namely, Siam/Thailand, the Philippines, Malaya/Malaysia and Indonesia, were aware of a regional consciousness and developed a regional concept. The study uses the conventional historical, chronological and analytical approaches. The time frame of the study is between the nineteenth century and the year 1976. In the nineteenth century the term ‘Southeast Asia’ was born and nationalists in each country became aware of a region in the colonial era, and in 1976 political leaders in the countries declared their goal to an ASEAN community with an ASEAN identity in the First Summit of ASEAN. While the study argues that Europeans, especially the British, were quite familiar with the term ‘Southeast Asia’ prior to the Second World War, the concept varied from writer to writer by the 1960s. Nevertheless, the British popular term had seldom been used among politicians and intellectuals in the region. Instead, the royal court in Siam/Thailand has been aware of the region of Asia/East, and identified them as a broad region. On the other hand, islanders in the maritime region had their own regional terms, and since the end of the nineteenth century, intellectuals in the region who accepted a Malay identity also began to have a regional consciousness based on the area that Malays dwelt. However, after the Second World War all the consciousness shifted to the region of Southeast Asia, which combined the mainland (called Further India before the war) with the maritime (called Malay Archipelago etc.). As the term Southeast Asia was politically used, such as in SEAC and SEATO, the four countries gradually attempted to dilute the politically-coloured term to a softer image through their economic and cultural co-operation, prior to the formation of ASEAN. While ASEAN was formed for the economic co-operation, the members strengthened their regional consciousness by embracing political discussions at the same time. To protect their national security, ASEAN countries became the centre to define their own regional concepts since the early 1970s. Consequently, the 1976 ASEAN summit started their project to form and invent an ASEAN community.